Cellular Internalization and Inhibition Capacity of New Anti-Glioma Peptide Conjugates: Physicochemical Characterization and Evaluation on Various Monolayer- and 3D-Spheroid-Based in Vitro Platforms - Baranyai, Zsuzsa; Biri-Kovács, Beáta; Krátký, Martin; Szeder, Bálint; Debreczeni, Márta L; Budai, Johanna; Kovács, Bence; Horváth, Lilla; Pári, Edit; Németh, Zsuzsanna; Cervenak, László; Zsila, Ferenc; et al. (Journal of medicinal chemistry, 2021)
Most therapeutic agents used for treating brain malignancies face hindered transport through the blood-brain barrier (BBB) and poor tissue penetration. To overcome these problems, we developed peptide conjugates of conventional and experimental anticancer agents. SynB3 cell-penetrating peptide derivatives were applied that can cross the BBB. Tuftsin derivatives were used to target the neuropilin-1 transport system for selectivity and better tumor penetration. Moreover, SynB3-tuftsin tandem compounds were synthesized to combine the beneficial properties of these peptides. Most of the conjugates showed high and selective efficacy against glioblastoma cells. SynB3 and tandem derivatives demonstrated superior cellular internalization. The penetration profile of the conjugates was determined on a lipid monolayer and Transwell co-culture system with noncontact HUVEC-U87 monolayers as simple ex vivo and in vitro BBB models. Importantly, in 3D spheroids, daunomycin-peptide conjugates possessed a better tumor penetration ability than daunomycin. These conjugates are promising tools for the delivery systems with tunable features.
Keywords: nosiče léků; nádorové buňky kultivované; Human Umbilical Vein Endothelial Cells; Glioblastoma; buněčné sféroidy; Rats; nádorové buněčné linie; oligopeptidy; Cell Line, Tumor; lidé; Spheroids, Cellular; glioblastom; Humans; nádory mozku; Brain Neoplasms; tuftsin; endoteliální buňky pupečníkové žíly (lidské); Cell-Penetrating Peptides; Animals; neuropilin-1; Neuropilin-1; protinádorové látky; Tuftsin; Antineoplastic Agents; zvířata; Blood-Brain Barrier; krysa rodu Rattus; lékové transportní systémy; penetrační peptidy; Tumor Cells, Cultured; hematoencefalická bariéra; Oligopeptides; Drug Delivery Systems; Drug Carriers